Prxgaruh Citra Merek terhadap Loyatitas Konsumen Starbucks Coffee di Yograkarta - Petra Surya Mega Wijaya (Jurnal Riset Manajemen dan Bisnis, 2008)
Todoy, the compailion in htsiness is getting hrder and horder, especially in the global crisis. A compofiy is rct only required to be effrcient, htt also to be able to be competitively acellent. The compory whbh is competitively qcellent is supposed a be able to win the competition.  Competitive qcellence may be achieved if the company does not only rely on its own tmiqueness, but also sorne uniqueness simultqteously owned fu that comporry. One of the company's tmiqueness, which can be used to rerchcompetitive ucellence, is brand image. Brand imoge is the compilation of association perceived by a anstomer towards a certain brand (Simarnora, 2004). Brand image consists of 3 dilnensions, i.e. 1) corporation image, 2) user image, and 3) product image. The resemch obiect was Starbucks Coffeeat Ambarubno Plaza Yogtakmta. This research aimed at testing the in/luence of corporation image, user image, ond pro&tct irnage on the cTtstomer loyalty of Starbucks Coffee.The sample was 100 respondents who have visited and bouglrt the products offered by Storbucl* Coffee in Yogtakarta. The Double Linear Regression analysis was employed to dnswer the reseorch obiectives. The research result uplained that there were positive atd significant influences between corporation image and pro&tct image on the c'ustorner loyalty of Snrbucb Coffee. An interesfingfind@was the result showing thatthere was negative and no significant intluences of user image on the customer loyalty of Snrbucfu Coffee.Keywotds: Brand Image, Corporation Image, (Jser Image, Product Image, Customer loyatty, Double Linear Regression, Starbucla Coffee